Harrison's infectious diseases - Kasper, Dennis L.; Fauci, Anthony S. 1940-; Harrison, Tinsley Randolph 1900-1978 (McGraw-Hill Medical, 2013)
Featuring a compilation of chapters related to infectious diseases that appear in Harrison's Principles of Internal Medicine, Eighteenth Edition, this concise, full-color clinical companion delivers the latest knowledge in the field backed by the scientific rigor and authority that have defined Harrison's. You will find content from renowned editors and contributors in a carry-anywhere presentation that is ideal for the classroom, clinic, ward, or exam/certification preparation. Current, complete coverage of need-to-know topics, including infections in organ systems, bacterial infections, viral infections, prion diseases, fungal infections, and protozoal infections. Two image-based chapters comprise atlases valuable to clinical assessment: rashes associated with fever and blood smears of the various stages of the parasites causing malaria and babesiosis. Helpful appendix of laboratory values of clinical importance.